Current State-of-the-Art and New Trends in Self-Assembled Nanocarriers as Drug Delivery Systems - Paliwal, Himanshu; Parihar, Akshay; Prajapati, Bhupendra G. (Frontiers in Nanotechnology, 2022)
Self-assembled nanocarrier drug delivery has received profuse attention in the field of diagnosis and treatment of diseases. These carriers have proved that serious life-threatening diseases can be eliminated evidently by virtue of their characteristic design and features. This review is aimed at systematically presenting the research and advances in the field of self-assembled nanocarriers such as polymeric nanoparticles, dendrimers, liposomes, inorganic nanocarriers, solid lipid nanoparticles, polymerosomes, micellar systems, niosomes, and some other nanoparticles. This self-assembled delivery of nanocarriers has been developed in recent years for targeting diseases. Some of the innovative attempts with regards to prolonging drug action, improving bioavailability, avoiding drug resistance, enhance cellular uptake, etc. have been discussed. The discussion about various delivery systems included the investigation conducted at the preliminary stage i.e., preclinical trials and assessment of safety. The clinical studies of some of the recently developed self-assembled products which are currently at the clinical trial phase or FDA approved.